NIGERIAN TRAFFICKING IN PERSONS REPORT: LESSONS FROM POLICY IMPLEMENTATION - USMAN MIKA'IL; MURTALA MUHAMMAD (CenRaPS Journal of Social Sciences, 2020)
Human trafficking is an international phenomenon. Trafficking in-person report the menace as a multifaceted and illicit trade that continues to generate billions of dollars to the global criminal networks annually. Nigerians especially females are trafficked abroad day in day out. This makes the most populous African nation among the largest source of victims to international trafficking networks. Nigeria tries to combat the menace by establishing a specialised anti-human trafficking agency. The agency is accountable for the implementation of the policy. However, putting policy into action presents thoughtful barriers that create implementation gaps. To date, there is nearly no study that looks into the activities of the Nigeria anti-trafficking agency using the trafficking in-person report. The investigation is a qualitative enquiry that uses an in-depth systematic review on human trafficking, which paid attention to putting anti-trafficking policy into practice. This is amongst a few studies that attempt to comprehend the state of human trafficking service delivery to the victims in Nigeria. It finds limited training, meagre resources, absence of awareness and corruption as the main barriers hampering efficient policy implementation.